Cardiovascular, muscular and perceptual contributions to physical fatigue in prevalent kidney transplant recipients. (6th January 2016) - Chan, Winnie; Jones, David; Bosch, Jos A.; McPhee, Jamie; Crabtree, Nicola; McTernan, Philip G.; Kaur, Okdeep; Inston, Nicholas; Moore, Sue; McClean, Andrew; Harper, Lorraine; Phillips, Anna C.; et al.
Summary: Physical fatigue is debilitating and common among kidney transplant recipients (KTRs). This study investigated the mechanistic aetiology of physical fatigue in this setting through examinations of muscle mass, muscular and cardiovascular function, and perceived exertion. The incidence of physical fatigue, its association with quality of life (QoL), and the predictors of perceived exertion, were evaluated. This single‐centre observational cross‐sectional study enrolled 55 KTRs. Muscle mass was quantified using dual‐energy x‐ray absorptiometry. Muscular function was assessed by jumping mechanography. Cardiovascular function (maximal oxygen consumption and oxygen pulse) was estimated during submaximal exercise testing, with perceived exertion determined using age‐adjusted Borg scale‐ratings. Physical fatigue was measured using Multi‐Dimensional Fatigue Inventory‐20. QoL was assessed using Medical Outcomes Study Short Form‐36. Demographic, clinical, nutritional, psychosocial and behavioural predictors of perceived exertion were assessed. Of clinical importance, increased perceived exertion was the only independent predictor of physical fatigue ( P = 0.001), with no association found between physical fatigue and muscular or cardiovascular parameters. Physical fatigue occurred in 22% of KTRs, and negatively impacted on QoL ( P < 0.001). Predictors of heightened perception included anxiety ( P < 0.05) and mental fatigue ( P < 0.05). Perception is a key determinant of physical fatigue in KTRs, paving the way for future interventions.